Projects towards climate action: Case of BRICS - Sharofiddin, Ashurov; Al-Shaghdari, Fahd Mohammed Obad; Mohd Noor, Azman; Mohammad, Habibullah (Routledge (Taylor & Francis), 2026)
This chapter explores BRICS nations’ financial cooperation, focusing on climate action projects that promote economic resilience, sustainable growth, and social impact. Central to these efforts are the New Development Bank and the Contingent Reserve Arrangement, which enhance economic stability and support climate-centric initiatives. The study further explains how BRICS, especially with its expansion to BRICS Plus, is positioning itself to influence global trade and finance through investments in green technologies, reducing reliance on Western financial systems. Emphasis is placed on how these efforts align with sustainable development and the economic inclusion of the Global South.